Cross-cultural adaptation and initial validation of the Brazilian-Portuguese version of the pediatric automated neuropsychological assessment metrics - de Amorim, Jaqueline Cristina; Kishimoto, Simone Thiemi; Elorza, Cibele Longobardi Cutinhola; Cavaletti, Flávia Alegretti; Marini, Roberto; Silva, Clovis Artur; Saad-Magalhães, Claudia; Fernandes, Paula Teixeira; Brunner, Hermine I.; Appenzeller, Simone (Frontiers in Psychology, 2022)
Automated batteries have been used in research and clinical practice, in the health area, and especially with chronic diseases, such as Systemic Lupus Erythematosus. The Pediatric Automated Neuropsychological Assessment Metrics battery, Ped-ANAM, allows tracking of cognitive functions. It can be applied to people over 9 years old. The aim of this study is to translate and present initial validation data from the Ped-ANAM into Brazilian-Portuguese. We translated the battery according to Beaton's guidelines. Psychometric properties were tested, internal consistency was analyzed by Cronbach's alpha coefficient, test-retest reliability by the intraclass correlation coefficient (ICC). Also, we measured the test execution speed at both times as a temporal stability. Principal component analysis (PCA) was used for structural validity. Evidence of validity based on relationships with other variables through correlations with Wechsler intelligence scales. All participants signed an informed consent form approved by the local ethics committee. A sample of two hundred and thirty individuals were included, from mean age 23 ± 11 years range = 9 to 60 years (65.22% females). A group of 51 subjects [from mean age 18 years range = 9 to 57 years; 30 were female (58.82%)] of the same sample were invited to test and retest, and other 54 subjects [from mean age 20.4 years range = 7 to 62 years; 36 were female (66.67%) subjects], for correlation with the Wechsler Intelligence Scale for Children and Adult. The internal consistency of the batteries (Cronbach's α= 0.890) and the test-retest reliability were excellent, from ICC 0.59 to 0.94, for correlation in velocity r=0.48 to r=0.90. There was no clustering in the principal components analysis. The Spearman correlations between the Wechsler scales showed results ranging from low to high correlation, which is expected they are batteries with a degree of similarity but not identical. The study showed evidence of reliability and initial validity, which makes the Ped-ANAM a reliable tool for screening cognitive function. Thus, future uses of the Ped-ANAM may promote the tracking of cognitive demands and contribute to the validation of data in other groups, enabling multicenter studies in Brazil with the population of patients with lupus.